2023
DOI: 10.3390/met13010156
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Layer Formation during Gas Nitriding of Remelted Ledeburitic Surface Layers on Unalloyed Cast Irons

Abstract: Unalloyed cast iron materials exhibit low tribological and corrosive resistance. In this respect, nitriding has a wide range of applications for steels. In the case of cast iron, the advantageous properties of nitrided layers are impaired by the presence of graphite. Electron beam remelting of cast iron surfaces prior to nitriding removes graphite. The homogeneous ledeburitic microstructure within the approx. 1 mm-thick remelted layer enables the formation of a dense compound layer during subsequent nitriding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Depending on the nitriding potential, γ' grew exclusively on the material surface during nitriding with K N = 1 atm −1/2 (KN1) and ε grew exclusively during nitriding with K N = 4 atm −1/2 (KN4). [21] This observation was consistent with the Lehrer diagram [34] valid for pure iron, which specified the formation of the observed iron nitrides from pure iron at the selected nitriding temperature of 540°C and the nitriding potentials mentioned.…”
Section: Microstructure Of the Nitrided Layers With And Without Prior...supporting
confidence: 89%
See 4 more Smart Citations
“…Depending on the nitriding potential, γ' grew exclusively on the material surface during nitriding with K N = 1 atm −1/2 (KN1) and ε grew exclusively during nitriding with K N = 4 atm −1/2 (KN4). [21] This observation was consistent with the Lehrer diagram [34] valid for pure iron, which specified the formation of the observed iron nitrides from pure iron at the selected nitriding temperature of 540°C and the nitriding potentials mentioned.…”
Section: Microstructure Of the Nitrided Layers With And Without Prior...supporting
confidence: 89%
“…[28,29] The SC formed along the eutectic cementite plates and also occurred in a duplex structure consisting of alternating cementite and SC lamellae. [21,30] The alloying elements contained in the cast iron (see Table 1) were not homogeneously distributed in the white-solidified microstructure. In accordance with the trends implied by the literature, [31][32][33] the EDS examination revealed that the eutectic cementite could be considered to be essentially Si-and Cu-free.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations